GROUP HUNTING: RELIGION, POLITICS, AND IDEOLOGY IN LATER STUART BRITAIN*. (29th October 2015) - Unknown
Abstract : Early modern groups did not necessarily proclaim themselves. When they did, they were not necessarily groups. The historian must decide when to analyse people as separate individuals and when their commonalities were great enough that they should be considered together. These judgements have been the source of frequent debate. At times, the disagreement has been over the proper label for a group – whether, for instance, 'puritans' should instead be called 'the godly'. In other cases, the very existence of a group has been called into question, with some doubting whether there was a 'Ranter' movement in the 1650s. Often, historians debate the coherence of a group, with one prominent scholar questioning whether the first whigs in the late 1670s were organized enough to deserve the appellation of a 'party'. The vigour of these debates suggests that some of our most important intellectual labours are done when we assign people to groups.